Analysis of Muhammad Baqir al-Sadr's Thoughts on Daya Anagata Nusantara (DANANTARA) as a Sovereign Wealth Fund (SWF) - Badrud Tamam; Moh. Mujibur Rohman; Iskandar Iskandar; Mega Ilhamiwati; Siti inayatul Faizah (Lan Tabur: JURNAL EKONOMI SYARIAH, 2026)
The establishment of Daya Anagata Nusantara (DANANTARA) as Indonesia's Sovereign Wealth Fund (SWF) reflects the country's efforts to optimize the management of strategic assets to support long-term development and national economic stability. Amidst the dominance of the global capitalist paradigm that emphasizes capital accumulation and market efficiency, an alternative framework of thinking is needed to ensure that SWF management remains oriented towards social justice and public welfare. In this context, the economic thinking of Muhammad Baqir al-Sadr is relevant to examine, particularly his ideas on the concept of public ownership, the role of the state as a representative of the people, and the rejection of exploitation and the accumulation of wealth by a small elite. This article focuses on a conceptual analysis of the relationship between al-Sadr's economic thinking and the characteristics of DANANTARA as an SWF in the context of the Indonesian economy. The purpose of this study is to identify the extent to which Muhammad Baqir al-Sadr's thinking can provide a normative and critical basis for the equitable management of DANANTARA as an SWF. The research methodology used is qualitative research with a normative-philosophical approach through a literature study of al-Sadr's works, Islamic economic literature, and regulations and policy documents related to SWFs in Indonesia. The results of the study show that the principles of public ownership and state responsibility in al-Sadr's perspective are in line with the objectives of establishing DANANTARA, as long as its management is not solely profit-oriented, but rather focused on the fair and sustainable distribution of economic benefits. Thus, al-Sadr's thinking has the potential to become an ethical framework in directing DANANTARA as an SWF that favors the public interest.